Evaluasi Proses Manajemen Program CSR Kemitraan (Studi Kasus Program Kemitraan dan Kebinaan Lingkungan PT. Madubaru) - Dwiyan Mayangsari; Mufid Salim; Virna Julia Kahar; Shella Aprilliya; Firhan Ardhiyansyah; Ragil Ilmiawan (Journal of Communication Sciences (JCoS), 2020)
CSR (Corporate Social Responsibility) can be defined as a form of corporate concern for the company's external stakeholders. CSR is a very important program to establish cooperation and gain trust from the community around the company. Through CSR programs, companies can contribute to facilitate and support community programs in various aspects such as the natural environment, social, and so forth. The importance of CSR as part of the company's activities is also recognized by PT. Madubaru. The objective of implementing this program is to create harmony between the company and the surrounding communities. PT. Madubaru itself has a CSR program in the form of a partnership program. The form of activities of the partnership program namely, in the form of long-term loans or working capital loans aimed at fostered partners of PT. Madubaru himself. The target of this program is Small and Medium Enterprises (SMEs) which fall within the criteria for the requirements. Retrieval of data in this study using interview techniques, and direct surveys in the field. In carrying out direct survey researchers visited PT. Madubaru in October 2019. PT Madu Baru conducted a CSR management process starting from Situation Analysis, Strategy, Implementation, and Evaluation. In implementing the partnership program at PT. Madubaru is running smoothly and by CSR planning theory, but external constraints are not running according to the company targets that have been determined.